Utilizing Theory of Planned Behaviour to increase intention to participate in hepatitis C treatment therapy among Methadone maintenance therapy clients (MMT) in Malaysia: A cluster randomised control trial - Mohd Hafiidz Baharudin; Siti Aisah Mokhtar; Ahmad Zaid Fattah Azman; Ahmad Iqmer Nashriq Mohd Nazan (PLoS ONE, 2025)
Introduction The World Health Organization (WHO) has targeted eliminating viral hepatitis as a public health problem by 2030. Thus, high-risk groups such as Methadone Maintenance Therapy (MMT) clients should be targeted for hepatitis C health intervention to increase intention for hepatitis C infection treatment. This study aims to evaluate the effectiveness of theory-based hepatitis C health education and learning module (HEAL) in increasing intention to participate in hepatitis C treatment among MMT clients in Malacca. Methods A single-blinded cluster randomised control trial was conducted among selected MMT clients from government health clinics in Malacca from July 2023 to February 2024. The clinics involved was randomly allocated into intervention and control groups. The intervention group received HEAL module developed based on the Theory of Planned Behavioural while the control group attended clinic session as usual. Generalized Estimating Equation (GEE) analysis was used for statistical analysis. Results GEE shows that there is significant interaction between time and group for both intention for hepatitis C treatment and knowledge on hepatitis C. Intervention group at immediately post intervention follow up had higher intention for hepatitis C treatment as compared to control group (β = 0.56, 95% CI = 0.12, 1.01, p-value < 0.01). However, there were no significant different in intention for hepatitis C treatment between the two group at 3-month post intervention follow up. Furthermore, intervention group had significant higher knowledge at immediately post intervention (β = 8.85, 95% CI = 7.35, 10.36, p-value < 0.001) and at 3-month post intervention (β = 5.25, 95% CI = 3.76, 6.75, p-value < 0.001) as compared to the control group. However, the knowledge level among the intervention group reduces at 3-month post intervention follow up as compared to knowledge level at immediately post intervention follow up. Conclusion HEAL module which utilizes motion video and group discussion was effective in increasing MMT client’s intention for hepatitis C treatment and knowledge about hepatitis C. However, future research should focus on finding effective strategies to ensure retention of the outcomes of HEAL module intervention over time.